PEMBELAJARAN PENDIDIKAN PANCASILA UNTUK MENANAMKAN NILAI TOLERANSI DENGAN MODEL PjBL BAGI SISWA KELAS IV SD NEGERI DEMANGAN - Angelica Dara Azalia; Paulus Wahana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the process, difficulties, strategy, and impact of Pancasila Education learning to instill tolerance values using the Project Based Learning (PjBL) model for Grade IV students at SD Negeri Demangan. This research uses a descriptive qualitative method. Data collection was conducted through observation, interviews, questionnaires, and documentation. The research subjects consisted of one Grade IV B classroom teacher and 27 Grade IV B students. The results show that: (1) the implementation of PjBL-based Pancasila Education learning was carried out systematically through planning, project implementation, presentation, and reflection stages, effectively fostering tolerance values through collaboration and social interaction among students; (2) the difficulties encountered included differences in student character, time limitations, and low student participation in group discussions, which were overcome through personal guidance, reinforcing group rules, and providing positive reinforcement; and (3) the implementation of PjBL had a positive impact on students, shown through increased ability to respect differing opinions, maintain harmony, cooperate, and understand each member's rights and responsibilities in group activities. Therefore, the PjBL model is proven effective in instilling tolerance values, cooperation, and social responsibility through meaningful learning experiences.